2020
DOI: 10.1038/s43246-020-00063-5
|View full text |Cite
|
Sign up to set email alerts
|

Face-selective tungstate ions drive zinc oxide nanowire growth direction and dopant incorporation

Abstract: Tailoring the elemental doping of inorganic nanowires remains an important challenge due to complex dopant incorporation pathways. Here we report that the face-selectivity of tungstate ions controls growth direction and dopant incorporation of hydrothermal zinc oxide nanowires. The introduction of tungstate ions on nanowire surface during synthesis unexpectedly enhances nucleation at sidewall 10 10 f g planes, while dopant incorporation occurs only on (0001) planes. This conflicting face-selective behavior lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Various fabrication methods have been investigated to obtain high-quality ZnO thin films and nanostructures on substrates. These methods can be classified into the following three types: (a) physical vapor deposition, including thermal evaporation, molecular beam epitaxy, sputtering, and laser ablation; (b) chemical vapor deposition (CVD), including metal–organic CVD, mist CVD, hot filament CVD, and atomic layer deposition; ,, (c) chemical solution synthesis including sol–gel synthesis, hydrothermal growth, and spray pyrolysis. Generally, the parameters of these synthesis methods are optimized to obtain ZnO thin films and nanostructures with the required physical and chemical properties, high stability, and compatibility using various substrates. However, parameter optimization generally involves a trade-off between the required properties.…”
Section: Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various fabrication methods have been investigated to obtain high-quality ZnO thin films and nanostructures on substrates. These methods can be classified into the following three types: (a) physical vapor deposition, including thermal evaporation, molecular beam epitaxy, sputtering, and laser ablation; (b) chemical vapor deposition (CVD), including metal–organic CVD, mist CVD, hot filament CVD, and atomic layer deposition; ,, (c) chemical solution synthesis including sol–gel synthesis, hydrothermal growth, and spray pyrolysis. Generally, the parameters of these synthesis methods are optimized to obtain ZnO thin films and nanostructures with the required physical and chemical properties, high stability, and compatibility using various substrates. However, parameter optimization generally involves a trade-off between the required properties.…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…Hydrothermal synthesis has been intensively investigated for the fabrication of nanostructures at low temperatures for applications such as light-emitting devices, solar cells, and sensors. ,,, In the hydrothermal growth of ZnO nanostructures, several parameters, including the pH of growth solutions, temperature, and ionic species, should be optimized to obtain the desired morphology and properties. Understanding the effects of these parameters is crucial for fabricating ZnO nanostructures to be used in harsh electronics. ,,, …”
Section: Fabrication Methodsmentioning
confidence: 99%
“…Thus, ZnO NWs and nanowalls provide unique face-selective electrostatic interactions by anisotropic crystal growth. 26,[59][60][61][62][63] and the long columnar shape (Fig. S2 †) implied abundant mplanes.…”
Section: Ir Spectra Of Adsorbed Nucleotides On the Zno Nwsmentioning
confidence: 99%
“…[16][17][18] Many growth parameters have been explored to manipulate the morphology of hydrothermally synthesized ZnO nanowires including the addition of auxiliary agents such as organic ligands, metal ion impurities and ammonia ions. [19][20][21][22][23][24] The solution-grown ZnO nanowires generally adopt the wurtzite crystal structure and grow along the c axis with a (0002) top facet and (1010) side facets. At pH = 11 basic conditions, it was found that the top facet is negatively charge and the side facets are positively charged, enabling control of the nanowire dimensions based on the facet-selective electrostatic interaction; 25 and therefore, the radial growth of colloidal nanowires can be effectively suppressed.…”
Section: Introductionmentioning
confidence: 99%